2018
DOI: 10.3389/fpls.2018.01335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil pH on the Growth, Reproductive Investment and Pollen Allergenicity of Ambrosia artemisiifolia L.

Abstract: Despite the importance of soil reaction for alien plant establishment, few and incomplete studies have included this key factor so far. In this study, we investigated the effects of soil pH on the germination, growth (plant height, width, dry weight, etc.) and reproductive investment (inflorescence size and n° of flowers) of Ambrosia artemisiifolia (common ragweed), an allergenic species that is highly invasive and alien in Europe, through a replicated experiment in controlled conditions. In addition, we deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(104 citation statements)
references
References 64 publications
(72 reference statements)
7
93
0
4
Order By: Relevance
“…This is also supported by the positive correlation between crop cover and application of P (as well as N) fertilizer in our dataset (Electronic Appendix 1). Although several relationships between certain soil properties and the abundance of ragweed are reported in previous studies (Pinke et al 2011(Pinke et al , 2013(Pinke et al , 2016(Pinke et al , 2018 and similar correlations reported by other authors (Hui-na et al 2014, Onen et al 2017, Gentili et al 2018, the importance of P reported here is a new finding. In our dataset the P content of the soil was not correlated with the other factors.…”
Section: General Predictors For the Whole Area Studiedsupporting
confidence: 90%
“…This is also supported by the positive correlation between crop cover and application of P (as well as N) fertilizer in our dataset (Electronic Appendix 1). Although several relationships between certain soil properties and the abundance of ragweed are reported in previous studies (Pinke et al 2011(Pinke et al , 2013(Pinke et al , 2016(Pinke et al , 2018 and similar correlations reported by other authors (Hui-na et al 2014, Onen et al 2017, Gentili et al 2018, the importance of P reported here is a new finding. In our dataset the P content of the soil was not correlated with the other factors.…”
Section: General Predictors For the Whole Area Studiedsupporting
confidence: 90%
“…It greatly influences the behavior of chemical elements and, along with organic matter (OM), is the most important parameter determining trace metal partitioning and aqueous speciation in soils [18]. It is considered of special importance in connection with nutrients [19] and micronutrients [20], and it is the key variable that affects plant growth [21]. It controls soil fertility, regulates soil biogeochemical processes, and influences the structure and functioning of terrestrial ecosystems [22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the interference in root growth, pH can change the nutrient absorption capacity, which may lead to mineral deficiency or toxicity by metals such as aluminum (Brown, Koenig, Huggins, Harsh, & Rossi, 2008; Gentili, Ambrosini, Montagnani, Caronni, & Citterio, 2018). Calcium may favor cell elongation and expansion, increasing root growth (Fageria & Moreira, 2011).…”
Section: Introductionmentioning
confidence: 99%